2007
DOI: 10.1525/mp.2007.25.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Production of Syncopated Rhythms

Abstract: THE PROCESSING OF COMPLEX, METRICALLY ambiguous rhythmic patterns, of the sort found in much popular music, remains poorly understood. We investigated listeners' abilities to perceive, process and produce complex, syncopated rhythmic patterns. Rhythmic complexity was varied along a continuum, quantified using an objective metric of syncopation suggested by Longuet-Higgins and Lee. Participants (a) tapped in time to the rhythms, (b) reproduced the same patterns given a steady pulse, and (c) recognized these pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
138
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 46 publications
5
138
0
2
Order By: Relevance
“…In the present study, individual participants achieved the highest tapping synchronization percentages when segregated layers were presented with indeterminate pitch, but these conditions also gave rise to the largest variance across participants. These findings are consistent with previous studies that found that degree of syncopation is a good predictor of synchronization performance (Fitch & Rosenfeld, 2007;Toiviainen & Snyder, 2003), and that musical training provides an advantage in hierarchical meter processing (Geiser et al, 2010;Palmer & Krumhansl, 1990).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, individual participants achieved the highest tapping synchronization percentages when segregated layers were presented with indeterminate pitch, but these conditions also gave rise to the largest variance across participants. These findings are consistent with previous studies that found that degree of syncopation is a good predictor of synchronization performance (Fitch & Rosenfeld, 2007;Toiviainen & Snyder, 2003), and that musical training provides an advantage in hierarchical meter processing (Geiser et al, 2010;Palmer & Krumhansl, 1990).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, when asked to tap along or reproduce nonisochronous sequences, participants perform better when the temporal structure is characterized by integer rather than non-integer duration ratios, e.g., 2:1 and 3:1 as opposed to 3:2 or 4:3 (Franěk, Radil, & Indra, 1988;Repp, London, & Keller, 2005). Finally, in rhythmic sequences that involve syncopation (as measured by the number of beats that are not explicitly marked by an event onset), performance accuracy decreases as the degree of syncopation increases (Fitch & Rosenfeld, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…(6) Note density quantifies how many notes per second the melody contains (with more notes, the melody is assumed to be more complex, which is related to the motor-limitations of performance and to the span of the short-term memory in general). (7) Rhythmic variation is the overall deviation of the note durations where higher variance suggests higher complexity (Fitch & Rosenfeld, 2007). (8) Metrical accent is a measure of phenomenal accent asynchrony where higher values indicate higher complexity (Fitch & Rosenfeld, 2007).…”
Section: Expectancy-violation Modelsmentioning
confidence: 99%
“…(7) Rhythmic variation is the overall deviation of the note durations where higher variance suggests higher complexity (Fitch & Rosenfeld, 2007). (8) Metrical accent is a measure of phenomenal accent asynchrony where higher values indicate higher complexity (Fitch & Rosenfeld, 2007). The differences between the principles can be illustrated with three examples taken from the Essen collection, all of which also belong to the D6 dataset.…”
Section: Expectancy-violation Modelsmentioning
confidence: 99%
See 1 more Smart Citation